The Islamic Education Through Scientific Approach: Learning and Character Building on Transmigration Territories Elementary School - Ahmad Suradi; Nilawati Nilawati; Ani Aryati (International Journal of Asian Education, 2021)
This article aims to reveal that the learning of Islamic education and scientific-based character is an attempt to neutralize the assumptions about the inability of teachers to develop students to their full potential. Likewise, the assumptions about the learning of Islamic education and manners only have ritual, ethical and moral dimensions so that students can verbally understand the teachings of Islam and are skilled at implementing them, but they do not appreciate the depth of their meaning. This research is qualitative; the informants are religious teachers and students through interview and observation techniques. The research results show that implementing Islamic education and character education through a scientific approach explores the field to find concrete examples of how to empathize with others and be devoted to parents and teachers. Furthermore, learning with a scientific approach, especially on students' character matter, has promising implications for shaping student morals for the better. It is because students are required to practice directly the phenomena that arise from the existing learning material. Therefore, experiments carried out through observation and making simple reports and then discussed in class groups are practical approaches to remember, understand,  and practice the messages in the material delivered.